The effects of extensive reading on students' incidental vocabulary acquisition : - Vương, Thị Thu Trâm (Can Tho University, 2008)
The aim of this study was to explore the effects of extensive reading on students' incidental vocabulary acquisition. According to a number of researchers, second language vocabulary can be learned incidentally while the learner is engaged in extensive reading or reading for meaning, inferring the meaning of unknown words.